A novel method of interference source direction-finding with an existing single antenna beam in communication satellites - Ma, Dingkun; Li, Hao; Wu, Ruixue; Li, Yinan; Lü, Rongchuan; Ma, Yan; Ding, Yi; Yang, Xiaojiao; Jiang, Tong; Yu, Xumin (Frontiers in Physics, 2023)
Interference has become a key factor for communication satellites performance currently, the location of interference source is one of the most important information to solve this problem. The paper raises an innovative method of interference source direction-finding suitable for communication satellites with existing single antenna beam by only one beam and one RF channel, the method utilizes the symmetries of antenna pattern to search interference source direction. Comparing the traditional position method with time-frequency synchronized muti-satellites or directing antenna array in one satellite, the method doesn’t need to add any special direction-finding payload in communication satellite, the method shares existing antenna and RF channel with communication system in satellite, the ability of interference source direction-finding is a software-defined function in communication processor, it has an excellent co-existence with other existing system in communication satellite. Computer simulation and out-field experiment results in this paper show that the method has excellent performance in high direction-finding resolution within large coverage and realization simplicity, providing a novel way to solve the problem of interference source direction-finding with the least complexity. The method has great value and promising application prospects in engineering practice to settle increasing interfere problems in communication satellites.